Analisis Kebutuhan Tenaga Rekam Medis di Rumah Sakit Jiwa Grhasia Yogyakarta - Mutiara Ginanty Putri; Ahmad Ahid Mudayana (International Journal of Healthcare Research, 2021)
Workload analysis is an effort to calculate the workload in a work unit by adding up all workloads and then dividing it by individual work capacity, because there are still many officers who have double jobs. This research was conducted to analyze the number of manpower requirements at the Grhasia Mental Hospital Medical Record Installation in Yogyakarta which will be adjusted to the existing workload. This study used a qualitative method where data collection was obtained by observation using work sampling techniques to describe patterns of activity / workload and the proportion of time spent carrying out activities as well as conducting in-depth interviews with informants and document review. Meanwhile, the calculation of labor requirements uses the Workload Indicator Staffing Needs (WISN) method. The results showed that the use of officers' working time for productive activities was 60.3%, non-productive activities were 19% and personal activities were 20.7%. The results of calculations using WISN, the optimal number of medical record personnel is 17 people compared to the current number of personnel of 8 people. So that the need for medical record unit personnel requires additional details with 1 person in the assembling section, 3 people in the filling section, 4 people in the coding section, and 1 person in the reporting section. Based on the results of WISN calculations, the need for medical record personnel at Grhasia Mental Hospital Yogyakarta in 2021 requires additional personnel.